Student Perspectives in Investing in Stocks to Grow Interest in Investing in the Investment Gallery of the Indonesia Stock Exchange Universitas Muhammadiyah Sidoarjo According to an Islamic View: Perspektif Mahasiswa Dalam Berinvestasi Saham Untuk Menumbuhkan Minat Berinvestasi Di Galeri Investasi Bursa Efek Indonesia Universitas Muhammadiyah Sidoarjo Menurut Pandangan Islam - Noviatus Sholihah; Wiwit Hariyanto (Academia Open, 2021)
Knowledge of stock investment can encourage someone to have a positive attitude so that it fosters student interest in investing. Students are also still wondering whether the investment is a halal transaction or not. The purpose of this study is to find out how the perspective of students in investing in stocks according to the Islamic view to foster interest investing in the IDX, Umsida. In this study, the method used is a qualitative method with data collection techniques carried out by interviews, observation and documentation. Informants in this study is students. The results of this study indicate that students who have invested in students have 3 symptoms, namely elements of knowledge, will and feelings. Meanwhile, students who have not invested already have one of the symptoms of 3 elements. The student's perspective in growing interest in investing according to the Islamic view is to increase knowledge about investment.